Insomnia and sleep duration on COVID-19 susceptibility and hospitalization: A Mendelian randomization study - Peng, Liuqing; Jing, Jiarui; Ma, Jun; He, Simin; Gao, Xue; Wang, Tong (Frontiers in Public Health, 2022)
Background: Sleep disturbance including insomnia and sleep duration is associated with an increased risk of infectious. With the ongoing coronavirus disease 2019 (COVID-19) pandemic, it is important to explore potential causal associations of sleep disturbance on COVID-19 susceptibility and hospitalization. Method: Insomnia and sleep duration were selected as exposure. Outcomes included susceptibility and hospitalization for COVID-19. Two sample mendelian randomization design was used to assess causality between sleep and COVID-19. Inverse variance weighted method was used as main analysis method to combine the ratio estimates for each instrumental variable to obtain the causal effect. Cochran’s Q statistic was used to test for global heterogeneity. MR-Egger and weighting median estimator (WME) were used as sensitivity analysis to ensure the stability and reliability of the results. MR-Egger intercept term was used to test the mean pleiotropy. In addition, the direct effects of insomnia and sleep duration on COVID-19 susceptibility and hospitalization were estimated using multivariable mendelian randomization (MVMR). Results: Univariate MR provided no evidence of a causal associations of insomnia on COVID-19 susceptibility (OR=1.10, 95%CI：0.95, 1.27; p=0.21) and hospitalization (OR=0.61, 95%CI：0.40, 0.92; p=0.02); as does sleep duration (ORCOIVD-19 susceptibility =0.93, 95%CI：0.86, 1.01; p=0.07; ORCOIVD-19 hospitalization =1.21, 95%CI: 0.99, 1.47; p=0.08). MVMR results showed that insomnia may be a risk factor for increased susceptibility to COVID-19 (OR=1.65, 95%CI: 1.34, 2.05; p<0.001); and sleep duration was also associated with increased COVID-19 susceptibility (OR=1.31, 95%CI: 1.18, 1.46; p<0.001). Conclusion: Insomnia and extreme sleep duration may risk factors for increased COVID-19 susceptibility. Relieving insomnia and maintaining normal sleep duration may be powerful measures to reduce COVID-19 infections.